FAKTOR-FAKTOR YANG MEMENGARUHI EMPLOYEE PERFORMANCE DIMEDIASI OLEH ORGANIZATIONAL COMMITMENT - SALSABILA EKA AZAHRA; KAREL TJAHJADI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this study is to analyze the effect of Empowerment, Intrinsic Motivation, and Authentic Leadership on Employee Performance with Organizational Commitment as a mediator in employees of the X School Transportation Management Unit.The sample in this study was 52 employees. This study uses purposive sampling technique. Data collection was carried out by distributing questionnaires to respondents and using a Likert scale. This study uses a quantitative approach with a total of 52 respondents. The data analysis method used SEM-PLS. Data collection was carried out by distributing questionnaires using Likert scale measurements. The method for analyzing data uses path analysis. Based on the results of the study, it can be concluded that Empowerment, Intrinsic Motivation, and Authentic Leadership have a direct effect on Employee Performance. And Organizational Commitment mediates the influence of Empowerment, Intrinsic Motivation, and Authentic Leadership have a direct effect on Employee Performance.